PENGARUH CARBON EMISSION DISCLOSURE (CED), CORPORATE SOCIAL RESPONSIBILITY (CSR), DAN GREEN ACCOUNTING TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING - Sugeng Hariadi; Rifa Mufticha Nurwanda (JURNAL LENTERA BISNIS, 2024)
This study aims to determine the effect of Carbon Emission Disclosure (CED), Corporate Social Responsibility (CSR) and Green Accounting on Firm Value with Profitability as an intervening variable. This research is a type of causality research with a quantitative approach. This study uses data on annual reports, sustainability, and energy sector finances on the ASEAN Stock Exchange website with a total of 22 companies. The sampling technique used purposive sampling and obtained 66 energy company data. The analysis method uses SEMPLS with SmartPLS 3.0 software. The results of this study indicate that 1) Carbon Emission Disclosure has no significant effect on firm value, 2) Corporate Social Responsibility has a significant effect on firm value, 3) Green Accounting has no effect on firm value, 4) Carbon Emission Disclosure has no significant effect on profitability, 5) Corporate Social Responsibility has a significant effect on profitability 6) Green Accounting has no effect on profitability, 7) Profitability has a significant effect on firm value, 8) Carbon Emission Disclosure through profitability has no significant effect on firm value. 9) Corporate Social Responsibility through profitability has no significant effect on firm value, 10) Green Accounting through profitability has no significant effect on firm value. Keywords: Carbon Emission Disclosure, Corporate Social Responsibility, Green Accounting, Profitability, Firm Value